Mediasi Kepuasan Wajib Pajak dalam Pengaruh Digitalisasi Perpajakan terhadap Kepatuhan Wajib Pajak - Yohana Yustika Sari; Fatimah Fatimah; Sustinah Limarjani; Diah Fitriaty; Melinda Wijaya (JWM (JURNAL WAWASAN MANAJEMEN), 2026)
Tax digitalization refers to the integration of digital technology to enhance the efficiency and effectiveness of tax administration processes, including taxpayer registration, tax payment, and tax reporting. The Banjarmasin City Government, through BPKPAD, has adopted digital tax innovations for local taxes and introduced the Bijak (Banjarmasin Integrasi Pajak) application at the end of 2023 to support taxpayers in conducting digital tax transactions. This study aims to analyze the impact of tax digitalization on local taxpayer compliance and to assess the mediating role of taxpayer satisfaction in this relationship. The research involved 100 registered taxpayers who have used the Bijak application. The findings reveal that tax digitalization positively influences taxpayer compliance. Furthermore, the results confirm that taxpayer satisfaction acts as a mediator between tax digitalization and taxpayer compliance, emphasizing the crucial role of user experience in strengthening the effectiveness of digital tax systems.